300 Stereotactic Radiosurgery With Versus Without Embolization for Brain Arteriovenous Malformations. (1st April 2022) - Chen, Ching-Jen; Ding, Dale; Lee, Cheng-chia; Kearns, Kathryn; Pomeraniec, Isaac J.; Ironside, Natasha; Kondziolka, Douglas S.; Trifiletti, Daniel M.; Liscak, Roman; Cockroft, Kevin M.; Lee, John Y. K.; Sheehan, Jason P.
Abstract : INTRODUCTION: Prior comparisons of brain arteriovenous malformations (AVMs) treated using stereotactic radiosurgery (SRS) with or without embolization were inherently flawed, due to differences in the pre-treatment nidus volumes. METHODS: We retrospectively reviewed International Radiosurgery Research Foundation AVM databases from 1987–2018. Patients were categorized into the embolization and SRS (E+SRS) or SRS alone (SRS-only) cohorts. The two cohorts were matched in a 1:1 ratio using propensity scores. Primary outcome was defined as AVM obliteration. Secondary outcomes were post-SRS hemorrhage, all-cause mortality, radiologic and symptomatic radiation-induced changes (RIC), and cyst formation. RESULTS: The matched cohorts each comprised 101 patients. Crude AVM obliteration rates were similar between the matched E+SRS versus SRS-only cohorts (48.5% vs. 54.5%; OR = 0.788, p = 0.399). Cumulative probabilities of obliteration at 3, 4, 5, and 6 years were also similar between the E+SRS (33.0%, 46.4%, 56.2%, and 60.8%, respectively) and SRS-only (32.9%, 46.2%, 56.0%, and 60.6%, respectively) cohorts (SHR = 1.005, p = 0.981). Cumulative probabilities of radiologic RIC at 3, 4, 5, and 6 years were lower in the E+SRS (25.0%, 25.7%, 26.7%, and 26.7%, respectively) versus SRS-only (45.3%, 46.2%, 47.8%, and 47.8%, respectively) cohort (SHR = 0.478, p = 0.004). Symptomatic and asymptomatic embolization-related complication rates were 8.3% and 18.6%, respectively. Rates of post-SRS hemorrhage, all-cause mortality, symptomatic RIC, and cyst formation were similar between the matched cohorts. CONCLUSION: This study refutes the prevalent notion that AVM embolization negatively affects the likelihood of obliteration after SRS.